PENGARUH MODEL PROJECT-BASED LEARNING TERHADAP KEMAMPUAN ANALISIS KEBAHASAAN TEKS RESENSI - Maulidatus Sa'adah; Siti Fatimah Zahara; Lailan Syafira Putri Lubis (TITIK DUA: Jurnal Pembelajaran Bahasa dan Sastra Indonesia, 2026)
This study aimed to determine the effect of the Project-Based Learning model on students’ ability to analyze the language features of review texts among eleventh-grade students at MAS Muallimin Univa Medan. The study employed a quantitative method with a quasi-experimental approach using a two-group pretest-posttest design. The sample consisted of 60 students, including 30 students in the experimental class and 30 students in the control class. Data were collected through tests measuring students’ ability to analyze the language features of review texts administered before and after the treatment. The data were analyzed using normality tests, homogeneity tests, and hypothesis testing through an independent samples t-test. The results showed that the mean score of students’ language feature analysis ability in the experimental class was 79.37, while the mean score in the control class was 76.67. The hypothesis testing results revealed a significance value of 0.012 (< 0.05), indicating that Ha was accepted and H0 was rejected. These findings demonstrate that the use of the Project-Based Learning model has a significant effect on students’ ability to analyze the language features of review texts. The model was proven effective in enhancing students’ engagement in the learning process through project-based activities that foster critical, collaborative, and analytical thinking skills. The implications of this study suggest that Project-Based Learning can serve as an alternative instructional model for teaching Indonesian language at the senior high school level, particularly in learning activities that require language analysis skills.